Heat integration of power-to-heat technologies: Case studies on heat recovery systems subject to electrified heating - Kim, Jin-Kuk; Son, Hyunsoo; Yun, Seokwon (Journal of cleaner production, 2022)
A systematic design methodology for the electrified supply of heat in process industries is developed to provide process design guidelines for economic and energy-efficient transition from a fossil-fuelled energy system to a renewable-based electricity system. The most appropriate strategy for the implementation of electrified sources for energy systems is proposed in the context of Heat Integration. Design implications related to the introduction of electrified sources for industries are fully investigated for the design of heat recovery systems between conventional fossil-fuelled systems and electrified systems. As the electricity-based heating systems allows more degrees of freedom for the design of the HEN (Heat Exchanger Network) than fossil-fuel-based systems, design complexities of HEN under electrification can be considerably reduced. This is illustrated with a few cases of heat recovery system in which capital cost and design complexities can be minimized by considering the electrified energy supply and their characteristics in an effective and integrated manner. Preliminary techno-economic assessment for electrified energy recovery systems is carried out to understand economic limitation of industrial electrification under current energy prices and its sensitivities. •Heat Integration of industrial energy systems subject to electrification.•Process design methods and guidelines for heat supply from electrified units.•Cost-effective strategies for the implementation of electrified heating.•Techno-economic impact of power-to-heat for process industries.